UJI KUALITAS VIDEO CONFERENCE JITSI BERBASIS CONTAINER PADA AMAZON WEB SERVICES (AWS) - Qadrian Pristiadi; Lukman Lukman (UNIB Press, 2023)
The use of video conferencing has increased in recent years. Even though now the trend of activities is returning to going offline, video conferencing is still widely used for various needs. However, the available video conferencing platforms have limitations, so users are not comfortable using them. The Jitsi platform is used because it is based on open -source and claims that Jitsi has better quality if it is built using its own server. QoS testing is conducted to determine the quality of JITSI if it is built on a container architecture using Amazon Web Services virtual machines. The QoS parameters tested are throughput, packet loss, delay, and jitter. QOS testing is carried out in 2 scenarios using a virtual machine and a mobile phone to join into video conference rooms. In scenario 1 the highest QoS values obtained include throughput: 3128Kbps, packet loss: 0.012%, delay: 2.39ms, and jitter: 2.39ms. In scenario 2 the highest QoS values obtained include throughput: 1778Kbps, packet loss: 0%, delay: 2.82ms, and 2.82ms jitter. Meanwhile, the use of server resources increases in proportion to the number of users who join each test. Keywords: Video conference; QoS; Cloud; Container; JITSI.